Spatial variability of soil properties in reclaimed strip-mined lands - Carvallo, Hugo Orlando; Ghevi, Hans Raj (Pesquisa Agropecuaria Brasileira, 2014)
Two fields on reclaimed mine sites in western North Dakota were chosen to determine the degree of variation on five soil properties and to estimate file sample sire necessary to identify the statistical distribution with a prescribed level of confidence. With very few exceptions, all the set of measured values were characterized by normal distribution. The methods used to establish normality resulted in a useful measure of the goodness-of-fit of the normal distribution for the set of measured values. Variability differed among soil properties and changed with depth. The variability of the soil properties was greater at the Consolidation Site than at the North American Site. At the Consolidation Site the sample sizes required to identify the means with an 80 percent confidence level with ± 10 percent precision for 0.01 ha were found to be 1, 3, 2, 7 and 18 for the 0.3 and 15 bar, available soil water, sodium adsorption ratio and electrical conductivity, respectively. For the same soil properties at the North American 0.01 ha area sampling requirements were 1, 1, 2, 2, and 1 soil samples, respectively. Identical methodology could be used to study spatial variability of properties in natural agricultural soils.
Keywords: soil sampling; reclaimed mined soils